A Literature Review on Spicule-Assisted Transdermal Delivery Systems (S-TDS) : Penetration Mechanistic and Translational Perspectives - Maimunah, Siti; Febriyanti, Alifia Putri; Fauziyah, Begum; Agus, Adhe Septa Ryant (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2025)
Introdiction: Spicules are microscopic needle-shaped structures derived from marine sponges or synthetic biomimetic materials that have recently attracted attention as an innovation in enhancing transdermal penetration in cosmetic dermatology. This structure is capable of temporarily disrupting the protective layer of the stratum corneum and forming high-density microchannels that facilitate the delivery of bioactive compounds such as peptides, hyaluronic acid, growth factors, and nucleotides to deeper skin layers. Aims: The purpose of this review article is to provide comprehensive information on penetration mechanistic and translational perspectives aspects of spicule-assisted transdermal delivery systems (S-TDS) as well as to describe the mechanisms of skin absorption, local distribution, and the resulting biological effects. Methods: This review was conducted through a literature study using databases including Scopus, PubMed, and ScienceDirect, focusing on publications from 2016 to 2025 with the keywords "spicule," "transdermal delivery," "pharmacokinetic," "pharmacodynamic," and "cosmetic dermatology." Result: Based on the literature, S-TDS have been shown to enhance skin permeability and prolong the retention time of active ingredients in the epidermis and dermis, leading to improve bioavailability and sustained biological response. Pharmacokinetic parameters based on literature include flux metrics, percentage penetration, tissue deposition, and duration of spicule. Pharmacodynamic parameters, spicules induce controlled micro-injuries that stimulates fibroblast proliferation, collagen synthesis, and skin remodelling, resulting in anti-aging and skin rejuvenation effects. Conclusion: The preclinical and clinical studies suggest that spicules can enhance the penetration of various bioactive molecules, with potential applications in therapeutic dermatology, anti-aging and whitening cosmetics, transdermal vaccination and immunotherapy and systemic delivery for chronic therapy.